88.3k views
14 votes
Show that the statement is true. If AB has endpoints A(2, −3) and B(−2, 3), then the midpoint M of AB is the origin.

User Filnor
by
5.0k points

1 Answer

4 votes

Answer:

See explanations below

Explanation:

Given endpoints A(2, −3) and B(−2, 3),

If M is the midpoint of AB

M(X, Y) = (x1+x2/2, y1+y2/2)

X = x1+x2/2

X = 2 + (-2)/2

X = 2-2/2

X = 0/2

X = 0

Get the Y coordinate;

Y = y1+y2/2

Y = -3+3/2

Y = 0/2

Y = 0

Hence the midpoint of AB is at (0,0) which is the origin,

User Melchor
by
4.5k points